Current State of the Art on the Antioxidant Activity of Sage (Salvia spp.) and Its Bioactive Components - Poulios, Efthymios; Giaginis, Constantinos; Vasios, Georgios K. (Planta Medica, 2020)
Common sage (Salvia spp., with the most common species Salvia officinalis) is an important medicinal and aromatic plant due to its bioactive components, secondary products of its metabolism. These components are mainly phenolics, terpenoids, polyphenols, and flavonoids. Many studies have identified their important role in fighting oxidative stress in cells and organisms, together with their anticancer, antimicrobial, and anti-inflammatory role. There are many methods measuring the antioxidant activity of sage phenolic components, usually based on radical scavenging of free radical species, such as 2,2-diphenyl-1-picrylydrazyl and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), and determining the absorbance of the reduced product by a photometric assay. In addition, there are several in vitro and in vivo studies determining the protection of sage extracts in cells in culture or animals, respectively, after induction of oxidative stress. In this review, results from the currently available studies that unravel the significant role of sage bioactive compounds, as antioxidant compounds, and the variety of methods used have been critically analyzed and discussed.
Keywords: Salvia officinalis; Lamiaceae; antioxidant activity; phenolic compounds; in vitro studies; in vivo animal studies; DPPH assay; ABTS assay